2022
DOI: 10.3390/nano12224029
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of 6-Mercaptopurine Loaded Liposomal Formulation for Enhanced Cytotoxic Response in Cancer Cells

Abstract: 6-Mercaptopurine (6-MP) is a well-known immunosuppressive medication with proven anti-proliferative activities. 6-MP possesses incomplete and highly variable oral absorption due to its poor water solubility, which might reduce its anti-cancer properties. To overcome these negative effects, we developed neutral and positively charged drug-loaded liposomal formulations utilizing the thin-film hydration technique. The prepared liposomal formulations were characterized for their size, polydispersity index (PDI), z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The PDI values of the prepared ITZ-loaded ufasomes ranged from 0.179 to 0.834. It was observed that most of the samples had PDI values lower than 0.5 (except formulae F2, F4, and F5), indicating that the method of preparation was appropriate and reproducible [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PDI values of the prepared ITZ-loaded ufasomes ranged from 0.179 to 0.834. It was observed that most of the samples had PDI values lower than 0.5 (except formulae F2, F4, and F5), indicating that the method of preparation was appropriate and reproducible [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The penicillin–streptomycin solution was from MOLEQULE-ON® in Auckland, New Zealand. All examined cells were kept in humidified incubator conditions of 37°C and 5% CO 2 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figures 2 and 3, as published. The confusion occurred during the preparation of the Figures, leading to a mix-up between the control sample and one of the studied samples (Figure 2A,D), and the control sample and one of the studied samples (Figure 3A).…”
Section: Error In Figurementioning
confidence: 99%